What are the Difficulties of Teachers in Implementing Integrated Thematic Learning on the Previous Curriculum in Elementary Schools? - Isnaini, Siti Nur; Sukma, Elfia; Ahmad, Syafri; Zen, Zelhendri (Mimbar Sekolah Dasar, 2024)
The educational curriculum is continuously changing according to technological developments. The Merdeka Curriculum is here to perfect the implementation of the 2013 curriculum. Implementation of the 2013 curriculum at the elementary school level is carried out through integrated thematic learning. This study aims to analyze the difficulties faced by teachers in implementing integrated thematic learning in the 2013 curriculum in elementary schools. This research uses a mixed-methods approach and uses a literature review technique to examine the difficulties of implementing integrated thematic learning. This mixed-methods study involved 133 elementary school teachers in Payakumbuh City as respondents. The research instrument was a closed statement questionnaire about the difficulties faced by the teacher and an open question questionnaire about the reasons and causes of the difficulties. The results of the research show that the main difficulties experienced by teachers in planning, implementing, and assessing integrated thematic learning are that teachers have difficulty in preparing learning media to facilitate the achievement of basic competencies (39.9%), teachers have difficulty connecting concepts between subjects so that the separation between subjects in the lesson is not very clear (50.4%), and teachers have difficulty assessing student portfolios (47.4%). Teachers say that they find it difficult to determine the right learning model, method, or strategy that covers all the material and students' needs. Teachers also have difficulty implementing integrated thematic learning with several subjects that require a lot of time.